YOCARDIAL BRIDGES OF THE HEART OF THE DROMEDARY CAMEL (Camelus dromedarius - A. M. Babiker, Marw; A. M. Taha, Ali (Journal of Veterinary Medicine and Animal Production, 2022)
Myocardial bridges were found in 90% of dissected adult hearts of thedromedary camel. Myocardial bridges were classified into two types according to their relation with the overbridged artery. In Type I, the descending interventricular subsinuosal or paraconal branches were bridged by one or two bands of cardiac muscle, in Type II, the descending interventricular subsinuosal or paraconal branches were noticed to dip in the myocardium without reappearing. Eight out of eleven hearts of fetuses had myocardial bridges (72.7%); seven hearts had myocardial bridges of Type I